Summarizing of modal monitoring of the process of cryogenic heaving of the ground in the Kirillo-Belozersky museum-preserve - V. O. Podborskaya; V. V. Nevecherya (Известия высших учебных заведений: Геология и разведка, 2015)
The features of geological engineering conditions of the territory of the Kirillo-Belozersky museum-preserve are characterized; they are emphasized to be very favorable for the development of cryogenic heaving (due to widely spread clay grounds of different genesis, high humidity of the ground). The results of observations of the depth of seasonal freezing of the grounds, snow depth, and vertical displacements of wall constructions of monuments are analyzed. The value of the depth of freezing inside the “cold” (unheated) monuments is established to significantly exceed the depth of seasonal freezing of the grounds on the exposed surface under the snow. Maximum depth of seasonal freezing in the interior of the “cold” monument is 190 cm. The cryogenic heave is revealed to lead to the seasonal, alternating movements (ripples) of the walls with amplitude up to 24 mm for the winter season. The basic control measures are suggested to eliminate the causes of the development of this process and ensure the stability of structures: the works for planning the territory, creation of drainage systems, changes in temperature regime of the interiors.